2014
DOI: 10.1017/s0007114514003341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dietary Approach to Stop Hypertension (DASH) diet on cardiovascular risk factors: a systematic review and meta-analysis

Abstract: The Dietary Approach to Stop Hypertension (DASH) is recommended to lower blood pressure (BP), but its effects on cardiometabolic biomarkers are unclear. A systematic review and meta-analysis of randomised controlled trials (RCT) was conducted to determine the effects of the DASH diet on cardiovascular risk factors. Medline, Embase and Scopus databases were searched from inception to December 2013. Inclusion criteria were as follows: (1) DASH diet; (2) RCT; (3) risk factors including systolic and diastolic BP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
286
2
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 490 publications
(317 citation statements)
references
References 47 publications
(247 reference statements)
15
286
2
14
Order By: Relevance
“…A meta-analysis of RCTs with durations that ranged from 2 to 24 wk showed that, overall, the DASH diet was associated with a significant decrease of plasma cholesterol and LDL but was not significantly associated with fasting plasma glucose (30) compared with the effects of control diets. An 8-wk RCT in 48 women with polycystic ovary syndrome in Iran showed that adherence to the DASH diet than to a control diet resulted in a significant decrease in serum triglycerides and VLDLs (31).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of RCTs with durations that ranged from 2 to 24 wk showed that, overall, the DASH diet was associated with a significant decrease of plasma cholesterol and LDL but was not significantly associated with fasting plasma glucose (30) compared with the effects of control diets. An 8-wk RCT in 48 women with polycystic ovary syndrome in Iran showed that adherence to the DASH diet than to a control diet resulted in a significant decrease in serum triglycerides and VLDLs (31).…”
Section: Discussionmentioning
confidence: 99%
“…El patrón de dieta mediterránea, con consumo predominante de legumbres, frutas y verduras, juega un papel importante en la prevención de dicho riesgo [20,23,24]. Una dieta equilibrada con un 50-60% de hidratos de carbono (evitando los de azúcares de rápida metabolización típicos de dulces, bollería, refrescos…), un 10-15% de proteínas y un 20-30% de grasas (evitando las saturadas y el colesterol), contribuye a optimizar la salud individual.…”
Section: Tabla 2 Porcentajes De Patologías Más Prevalentes Entre La Munclassified
“…cluster analysis) have been linked to reduced risk of common age-related diseases (e.g. CVD, stoke and dementia) (46)(47)(48)(49) and mortality (50,51) . Compared with less healthy DP, healthy DP are characterised by higher intake of beneficial foods (e.g.…”
Section: Dietary Patterns and Health In The Very Oldmentioning
confidence: 99%